Communication Strategy in Health Promotion to Increase Family Planning Participation at Rawasari Community Health Center - Melva Ayu Sundari Barus; M. Ridwan; Silvia Mawarti Perdana (Jurnal EduHealth, 2023)
The increase in family planning participation at the Rawasari Community Health Center has decreased from 2018-2020. Judging from the data obtained from the Jambi City Health Service, in 2018 family planning participation in the Rawasari Community Health Center work area reached 84.3%, in 2019 family planning participation reached 74.2%, and in 2020 family planning participation reached 68.9% . In circumstances like this, an appropriate form of health strategy from Health Promotion officers is needed to increase Family Planning participation. This research aims to determine health promotion communication strategies in increasing family planning participation at the Rawasari Community Health Center. . The type of research used is qualitative research with a case study design. The selection of research informants was purposive with 13 informants. Data collection takes the form of interviews. The results of the research show that the communication strategy used in health promotion at the Rawasari Health Center is planning outreach activities, implementing outreach activities and monitoring after the outreach is carried out.